Evaluation of Nurses’ Evidence-based Practice at Primary Health Care Centers in Baghdad City (Medico Legal Update, 2020)
Objectives: The study aims at evaluating the nurses’ evidence-based practices at primary health care centersin Baghdad City.Methodology: A descriptive design is carried out at Baghdad City’s primary health care centers from January2en 2019 to June 1st 2020. One instrument is developed for the purpose of the study. A Non-probability, multistage purposive sample of (52) staff nurses, who are working at primary health care centers in BaghdadCity. The instrument is concerned with the evaluation of nurses’ evidence-based practices through (43)items which are divided in to five main domains of attitudes, knowledge, beliefs, readiness and applicationsof evidence-based practices. Content validity of the questionnaire is determined by panel of (10) expertsand Internal consistency reliability, Split-half technique, is obtained through Cronbach alpha correlationcoefficient. Data are collected through the use of the study instrument and the interview technique as meansof data collection. Data are analyzed through the use of descriptive statistical data analysis approach offrequencies, percentages, total scores and ranges.Results: The study findings indicate that the majority of the staff nurses have experienced poor level ofknowledge, attitudes, beliefs, readiness and application as dimensions of nurses’ evidence-based practices.Conclusion: The study findings depict that staff nurses have experienced inadequate evidence-basedpractices at primary health care centers.Recommendation: Planned training sessions can be designed, constructed and implemented to staff nursesat the primary health care centers relative to evidence-based practices.